CORRELATION BETWEEN BMI, DENTAL CARIES AND SALIVARY BUFFER CAPACITY IN A SAMPLE OF CHILDREN FROM MURES COUNTY, ROMANIA - Anamaria, Bud; Chibelean, Manuela; Pacurar, Mariana; Esian, Daniela; Monica-Cristina, Muica (Nagy-Bota); Bud, Eugen (European Scientific Journal, ESJ, 2015)
Both dental caries and malnutrition in children are serious public health problems with diet as a common risk factor. The aim of this study is to investigate the relationship between dental caries, Body Mass Index (BMI) and salivary buffer capacity in children. Materials and Method: The first part of the study was conducted on 144 children, aged between 6 and 12 years, examined in the Pediatric Dentistry Department of UMF Tirgu Mures. Nutritional status was assessed using BMI in accordance with the recommendations of the World Health Organisation. The sample was divided into four groups based on BMI: underweight, normal weight, overweight and obese for age. Dental caries were evaluated using the DMFT (Decayed Missing Filled Teeth) index for permanent dentition and dmft (decayed missing filled teeth) for deciduous dentition. Salivary buffer capacity was recorded with CRT Buffer Strips from Ivoclar Vivadent. Results: The mean age of the sample was 9.11 ± 0.19 years, the mean dmft was 2.58 ± 0.26 and mean DMFT 1.76 ± 0.2. The underweight group presented a significantly higher dmft index compared to the other groups. A negative correlation between the salivary buffer capacity and the caries index was found. Conclusions: Because the results of this preliminary study show a higher caries incidence in underweight children, the relationship between dental caries and malnutrition should be further investigated. Dentists and physicians treating children should consider malnutrition as a risk factor for dental caries.